Surgical Reconstruction of the Aorto–Left Ventricular Junction Using a Bovine Xenopericardial Patch in Prosthetic Aortic Valve Infective Endocarditis: A Case Report - Barno B. Sobirov; Rodion O. Skvarskyi; Liliana M. Hrubyak; Anatoliy A. Sokol; Nataliia V. Shchotkina; Oleksii A. Krykunov (Ukrainian Journal of Cardiovascular Surgery, 2025)
Background. Prosthetic aortic valve infective endocarditis (PVE) complicated by a circular annular abscess with complete disruption of the aorto–left ventricular junction (ALVJ) represents a major surgical challenge. Although bovine xenopericardial patches have previously been used for annular reconstruction in complex cases of infective endocarditis (IE), this report, for the first time, describes the use of a domestically manufactured bovine xenopericardial patch produced in Ukraine. The case highlights its practical applicability and potential significance for cardiac surgeons in Eastern Europe.Case Presentation. A 36-year-old man, who had previously undergone aortic valve replacement with a mechanical prosthesis (SJM #25) and supracoronary ascending aortic banding through a mini-J sternotomy in 2020, was admitted in May 2025 with complaints of fever, palpitations, memory impairment, and signs of systemic inflammatory response syndrome. Blood cultures grew Streptococcus pneumoniae. Echocardiography and computed tomography confirmed PVE complicated by a circular annular abscess and severe paravalvular regurgitation. After initial antibiotic therapy aimed at controlling bacteremia, the patient was referred to our center.Intraoperatively, a circular annular abscess with complete disruption of the ALVJ was found. The infected prosthesis was explanted along with the surrounding infected tissues, and meticulous local debridement was performed using antiseptic solutions. The ALVJ defect was reconstructed with a 7 × 1.5 cm bovine xenopericardial patch of domestic production (Glutaflex®, Ukraine). Subsequently, a new mechanical prosthesis (Carbomedics #23) was implanted. The aortotomy was closed, and the previously implanted vascular graft was reused for ascending aortic banding. Postoperatively, the patient required temporary pacing. At the 3-month follow-up, he remained in satisfactory clinical condition, with no evidence of residual infection or prosthetic valve dysfunction.Conclusions. This case demonstrates that bovine xenopericardial patches of domestic manufacture can be effectively used for annular reconstruction in IE complicated by periannular abscess formation. The material exhibited excellent intraoperative handling characteristics, biocompatibility, and accessibility, making it a promising and cost-effective alternative for cardiac surgeons, particularly in resource-limited settings.